A systematic literature review of factors influencing marital readiness - Icha Herawati,; Suzana Mohd Hoesni,; Jamiah Manap,; Nor Azzatunnisak Mohd Khatib, (Penerbit Universiti Kebangsaan Malaysia, 2025)
There is a risk of bias in the research since current literature review frameworks frequently lack measurement of the volume of literature, guidance on keyword inclusion, confidence in detecting knowledge gaps, and framing of research objectives. This calls into question the review's legitimacy and dependability. In order to overcome these difficulties, we want to enhance the systematic literature review (SLR) approach, which begins with a literature review and is then followed by another literature review. The researchers used a systematic literature review approach, the Preferred Reporting Items for Systematic Reviews and Meta-Analysis (PRISMA), to obtain relevant publications related to young people's marriage readiness. This process was divided into three main stages: identification, screening, and eligibility. Web of Science (WoS) and Scopus were the two main databases used in the study, containing over 33,000 journals spanning over 256 disciplines, such as psychology, environmental studies, developmental studies, and integrative social sciences. Primary research, psychological marriage readiness, readiness to marry, adolescent and young adult populations aged 1 to 25 years, and papers in English were the inclusion criteria for this study. Based on prior research findings, it has been shown that various aspects, including financial, emotional, sexual, personality, and mental readiness, are significant determinants of a person's marital readiness. This comprehensive literature review indicates that marriage readiness is influenced by three key aspects: individual, financial, and social factors. The results indicate a need for additional research on these factors.